Portuguese Fight Against Match-Fixing: Which Policies and What Ethic? - Moriconi, M.; Almeida, J. P. (Sport Integrity: Ethics, Policy and Practice, 2020)
Sport Integrity examines sports integrity from a range of disciplinary perspectives that will help to enhance the reader’s understanding of this burgeoning problematic in sports management. Securing and promoting the integrity of sport has become one of the critical tasks for the governance and management of sport at professional, elite and non-elite levels. Threats to the integrity of sport manifest themselves in an array of guises, and include problems such as match-fixing, corruption, and the poor governance and management of sport. To reflect these diverse difficulties, this volume brings together authors from different nationalities to examine specific problems from a range of disciplinary perspectives. Together, these contributors enhance the empirical and theoretical foundations of sports integrity and place ethical considerations at the heart of the discussions to improve the management of sport. Sport Integrity will be of great interest to scholars and practitioners of sport management, sport and ethics and sports governance. The chapters were originally published as a special issue of the Journal of Global Sport Management.